Effects of stitch density, thread tension and using conductive yarn as upper or lower thread on reading performance of embroidered rfid tag antennas - ESMER, GÖKHAN BORA (My University, 2022)
Textile-based Radio Frequency Identification (RFID) tags are widely used in diﬀerent applications such as sensing, localization, and identification applications. Embroidery is one of the methods in textile-based RFID tag production. The embroidered RFID tags are generally used in the follow-up of textile raw material production and inventory, and laundry of commercial textiles. They capture the transmitted electromagnetic wave and generate a new one with a special coding that includes the required information about the item. Therefore, the fabrication parameters of the embroidered antennas are important in terms of durability, cost, and working performance. The conductivity of an embroidered antenna depends on the conductivity of the thread, stitch density, thread tension, and sewing method of the embroidery. In this study, the effect of stitch density, thread tension, and using conductive yarn as needle (upper) or bobbin (lower) thread for embroidered RFID antennas were examined using a polyester yarn twisted with stainless steel that is plain stitched on cotton fabric. The read range performances of the samples were tested with an integrated circuit (IC) by using an indoor RFID reader. It was seen that the optimised stitch density has a significant impact while it was determining the amount of conductive element due to the length of the yarn. Additionally, using conductive yarn as lower thread gave nearly 50% better results in signal strengths.
Keywords: Tekstil Mühendisliği ve Teknolojisi; Diğer; Mühendislik ve Teknoloji; Textile Engineering and Technology; Other; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Malzeme Bilimi; MALZEME BİLİMİ, TEKSTİL; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE; MATERIALS SCIENCE, TEXTILES